The Soft Skill Elements in an On-Job Training (OJT) (Organisation) Assessment Rubric for Construction Technology Students in Malaysian Vocational Colleges - Abdul Musid, Nurhafizah; Mohd Affandi, Haryanti; Abas, & Nor Haslinda (Journal of Technical Education and Training, 2018)
During on-Job Training (OJT), students are assessed by using the OJT (Organisation) assessment rubric. However, soft skill elements in the current assessment rubric are quite general in assessing students according to the job scope for Diploma in Construction Technology. The items in the current assessment rubric are not specific to assess soft skills of site supervisors which are important in the construction industry. Therefore, this study aims to identify the soft skill elements for OJT (Organisation) assessment rubric for Construction Technology students. The research design for this study is a survey that was carried out quantitatively through questionnaires involving contractors of G4 to G7 as the population of this study and administered to 180 contractors by using simple random sampling. After document analysis and expert validation process, five items were selected to be the constructs of soft skills and 21 items were chosen to be the elements for soft skills. From the Rasch Model analysis which referred to the Infit and Outfit values, one item was discarded which was Item C05 because it showed out-of-range values for both the Mean Square Infit and Outfit as well as the Z Standard value for Infit and Outfit. This finding was validated by experts. As a result, only 20 elements were accepted to be elements of the OJT (Organisation) assessment rubric. However, according to the item polarity analysis, all 21 elements were accepted to be elements in the OJT (Organisation) assessment rubric. The data analysis also indicated that both item and person reliability were good. The five constructs identified from this study were communication skill, critical thinking and problem-solving skill, teamwork, ethics and professional moral and leadership skill. In conclusion, this study was able to identify specific soft skills for site supervisors which could help to solve the problem of the general assessment elements in the current OJT rubric. Students may use these elements as a reference for job scope during OJT. Therefore, it is suggested to conduct a study for determining the descriptors for the soft skill elements.